The repetitive cytoskeletal protein H49 of Trypanosoma cruzi is a calpain-like protein located at the flagellum attachment zone - Galetovic, Alexandra (2010)
Paracoccidioides brasiliensis causes paracoccidioidomycosis, a systemic mycosis in Latin America. Formamidases hydrolyze formamide, putatively plays a role infungal nitrogen metabolism. An abundant 45-kDa protein was identiﬁed as the P. brasiliensis formamidase. In this study, recombinant formamidase was over-expressed in bacteria and a polyclonal antibody to this protein was produced. Weidentiﬁed a 180-kDa protein species reactive to the antibody produced in miceagainst the P. brasiliensis recombinant puriﬁed formamidase of 45 kDa. The180-kDa puriﬁed protein yielded a heat-denatured species of 45 kDa. Both protein species of 180 and 45 kDa were identiﬁed as formamidase by peptide massﬁnger printing using MS. The identical mass spectra generated by the 180 and the45-kDa protein species indicated that the fungal formamidase is most likely homotetrameric in its native conformation. Furthermore, the puriﬁed formami-dase migrated as a protein of 191 kDa in native polyacrylamide gel electrophoresis, thus revealing that the enzyme forms a homotetrameric structure in its native state. This enzyme is present in the fungus cytoplasm and the cell wall. Use of a yeast two-hybrid system revealed cell wall membrane proteins, in addition to cytosolic proteins interacting with formamidase. These data provide new insights intoformamidase structure as well as potential roles for formamidase and its interaction partners in nitrogen metabolism.